Pendugaan masa simpan beras rendang dalam kemasan kertas minyak dan edible film tapioka menggunakan metoda akselerasi - Fajar Restuhadi; Dewi Fortuna Ayu; Winda Kusuma Dewi (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Beras rendang is a traditional food from Payakumbuh, West Sumatra. Beras rendang is made from white glutinous rice flour, which is roasted until dried and then mixed with liquid sugar and coconut milk, then cooked in a big pan. Since it is rich in fat from coconut milk, it can easily turn rancid during storage. Beras rendang is usually packed with oil-paper, but the nature of its glutinous rice ingredient makes it sticky enough to the paper and hard to peel off later. Therefore, this study is performed to use tapioca edible film as an alternative packing to the paper. The shelf life of beras rendang, which is packed with the paper compared to tapioca edible film, was estimated in this research. Then, the acceleration method was conducted by storing beras rendang for 30 days at three different temperatures, i.e., 30, 35, and 40°C, to estimate the shelf life of beras rendang. The parameters observed were sensory assessments of rancidity and thiobarbituric acid (TBA) values of beras rendang during storage. Data were analyzed using linear regression, then the equations obtained were used to calculate the shelf life of beras rendang at normal temperature (27°C). Based on rancidity sensory, the beras rendang shelf life packed with edible tapioca film was 59.26 days on the zero-order reaction with the regression equation of y = -4542.9x + 11.545, activation energy of 9,022.19 cal.mol-1, and quality degradation rate of 0.027 quality unit per day. Meanwhile, based on the TBA value, the beras rendang shelf life packed with the paper was 45.15 days on the zero-order reaction with the regression equation of y = -1991.7x – 2.3267, with an activation energy of 3,955.51 kal.mol-1, and quality degradation rate of 0.013 quality unit per day. It is found that beras rendang stored using edible tapioca film had a longer shelf life than paper packing. Therefore, the edible tapioca film as a packing alternative shows more advantages than paper packing in terms of its ability to prolong the shelf life, and its convenience to consume the beras rendang without needing to peel it off, because the film is edible.